Posttraumatic Stress Symptoms and Posttraumatic Growth in Mothers of Children With Intellectual Disability – The Role of Intrusive and Deliberate Ruminations: A Preliminary Report - Katarzyna Kiełb; Kamilla M. Bargiel-Matusiewicz; Ewa Pisula (Frontiers in Psychology, 2019)
BackgroundThe aim of this study was to find out if mothers of children with intellectual disability (ID) demonstrate symptoms of posttraumatic stress and posttraumatic growth (PTG), and to define the role of intrusive and deliberate ruminations in this area.MethodsThe questionnaire-based study included 85 mothers of children with ID. Three standardized questionnaires were used: Impact of Event Scale-Revised, PTG Inventory, Event-Related Rumination Scale.ResultsRelative to the population norm in Poland, 52% of mothers of children with ID demonstrated at least moderate level of symptoms of posttraumatic stress. The mean level of PTG was high in this group. Intrusive ruminations and mothers’ age served as a predictor for posttraumatic stress symptoms (PTSS). None of the types of rumination correlated with PTG.ConclusionMothers of children with ID demonstrated symptoms of both posttraumatic stress and PTG. Intrusive ruminations proved to be significant predictors for PTSS.